2007
DOI: 10.2485/jhtb.16.1
|View full text |Cite
|
Sign up to set email alerts
|

Biological Analysis of a Candidate Stem Cell-KUSA/A1 cell-for Bone Tissue Engineering

Abstract: Abstract:The basic principle of bone induction for tissue engineering is to use stem cells, growth factors and organic matrix. KUSA/A1 cell is an example of bone marrow stromal stem cell, capable of differentiating into osteoblasts, chondrocytes and myotubes under inducing conditions. It has been reported that mature KUSA/A1 osteoblasts cultured in osteogenic condition, were able to induce a few bone formation in collagen hybridized PLGP sponge in vivo. This may be due to their low proliferation potential ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Because two moles of calcium ions quantitatively bind to a mole of Alizarin red S reagent,26 this staining method is useful in the identification of in vitro calcification with a high sensitivity. Previously, we have reported that KUSA/A1 cells are not capable of producing mineralized nodules cultured in alpha medium 23. Our observations demonstrated that CaTiO 3 –CaCO 3 , CaTiO 3 – a C, and HA induced calcification by KUSA/A1 cells cultured in alpha medium (Fig.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Because two moles of calcium ions quantitatively bind to a mole of Alizarin red S reagent,26 this staining method is useful in the identification of in vitro calcification with a high sensitivity. Previously, we have reported that KUSA/A1 cells are not capable of producing mineralized nodules cultured in alpha medium 23. Our observations demonstrated that CaTiO 3 –CaCO 3 , CaTiO 3 – a C, and HA induced calcification by KUSA/A1 cells cultured in alpha medium (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…Previously, we have reported that KUSA/A1 cells are not capable of producing mineralized nodules cultured in alpha medium. 23 Our observations demonstrated that CaTiO 3 -CaCO 3 , CaTiO 3 -aC, and HA induced calcification by KUSA/ A1 cells cultured in alpha medium (Fig. 6).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The KUSA-A1 mesenchymal cells were acquired from the Japanese Collection of Research Bioresources Cell Bank (JCRB, Osaka, Japan). KUSA-A1 is a bone marrow stromal stem cell line capable of differentiating into osteoblasts, chondrocytes, and myotubes under inducing conditions. , The KUSA-A1 cells were first cultured and incubated in an osteoblast-inducer medium consisting of 4.5 g/L of glucose DMEM ( d -glucose, l -glutamine, phenol red, and sodium pyruvate) supplemented with 10% fetal bovine serum. Cells were allowed to proliferate within Petri dishes for 24 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…KUSA/A1 cells, a bone marrow stromal cell line, are capable of maintaining an immature stage when cultured in α-MEM even at high cell proliferation rates. Such a cell line solely induces mineralized nodules when cultured in specifi c osteogenic medium 29,30) . Thus, to determine CaTiO 3 -CaCO 3 effect on KUSA/A1 response, the cells were cultured in α-MEM together with the different compounds synthesized.…”
Section: Discussionmentioning
confidence: 99%